Control of sheath blight of rice by plant extracts - ANSARI, M.M. (Indian Phytopathology, 2002)
Antifungal activity of Trachispermum ammi, Cymbopogon citratus, Ocimum sp., Mentha sp., Rauwolfia sp., Lawsonia inermis and Vitex trifolia was tested against Rhizoctonia solani (causal organism of sheath blight of rice). T. ammi (seed) and Ocimum sp. (leaves) extracts were fungicidal whereas the other extracts had fungistatic activity. Sprays of T. ammi and Ocimum sp. extracts at 1:20 dilutions reduced the disease by 72.25 and 69.58%, respectively.